2018
DOI: 10.1071/sr18167
|View full text |Cite
|
Sign up to set email alerts
|

Organic carbon and nitrogen contents and their fractions in soils with onion crops in different management systems

Abstract: The use of plant species in rotation or succession of crops can increase C and N contents and their fractions in the soil. The objective of this study was to evaluate the effect of using soil cover crops in succession and rotation with onion crops in different soil management systems on the total organic carbon (TOC), total nitrogen (TN), and C and N fractions in soil aggregates, and bulk soil. The experiment was implemented in April 2007 with eight treatments: succession of onion and maize in a no-tillage sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 25 publications
1
11
0
1
Order By: Relevance
“…The lowest TOC contents in CTS always occurred in the bulk soil compared with TOC in aggregates. Ferreira et al (2018) found higher TOC contents in the bulk soil in CTS. That probably was due to the rupture of soil aggregates, which accelerated the decomposition of SOM protected inside aggregates, leading to increases in the SOM decomposition rate and lower TOC contents in the bulk soil.…”
Section: Total Organic Carbon In Soil Aggregates and Bulk Soilmentioning
confidence: 78%
See 2 more Smart Citations
“…The lowest TOC contents in CTS always occurred in the bulk soil compared with TOC in aggregates. Ferreira et al (2018) found higher TOC contents in the bulk soil in CTS. That probably was due to the rupture of soil aggregates, which accelerated the decomposition of SOM protected inside aggregates, leading to increases in the SOM decomposition rate and lower TOC contents in the bulk soil.…”
Section: Total Organic Carbon In Soil Aggregates and Bulk Soilmentioning
confidence: 78%
“…Cover crop species improve soil physical and chemical attributes in onion fields (Loss et al, 2017;Comin et al, 2018a;Santos et al, 2018;Ferreira et al, 2018) as well as soil biological properties (Silva et al, 2014). They also lead to lower weed emergence, affecting onion yield and quality (Vilanova et al, 2014;Oliveira et al, 2016;Comin et al, 2018b;Souza et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison with plow tillage, no tillage for six years resulted in a 5.3 Mg ha -1 increase in the SOC stock at the 0–10 cm soil depth, and 38% of the SOC accumulation occurred in the MOC fraction [ 23 ]. Ferreira et al [ 24 ] shows that the MOC concentration under no tillage in the 0–5 cm soil layer was lower than that under plow tillage, whereas Plaza et al [ 25 ] reports that the MOC concentration was16% higher in no tillage plots than in plow tillage plots. However, Blanco Moure et al [ 26 ] showed that no change in MOC concentrations under tillage practices occurred under rainfed Mediterranean conditions.…”
Section: Introductionmentioning
confidence: 99%
“…A literatura reporta que o cultivo de cebola em SPC provoca profundas alterações em atributos edáficos do solo, além de reduzir a disponibilidade de nutrientes às plantas e o seu conteúdo de matéria orgânica (Loss et al, 2015, Santos et al, 2017Comin et al, 2018;Ferreira et al, 2018).…”
Section: Introductionunclassified